Ethnic Differences Identified by Pain Sensitivity Questionnaire Correlate With Clinical Pain Responses. Issue 2 (1st February 2018) - Bell, Brooke A.; Ruscheweyh, Ruth; Kelley, Bernard Joseph; Ness, Timothy J.; Vetter, Thomas R.; Sellers, Alethia Baldwin
Abstract : Background and Objectives: The Pain Sensitivity Questionnaire, English version (PSQ-E), is predictive of pain-related responses to experimental stimuli. Ethnic differences have been noted in experimental measures of pain sensation using quantitative sensory testing. The present study sought to determine if the PSQ-E also identified similar ethnic differences. Methods: Fifty-seven subjects who self-identified as African Americans (AAs) and who were scheduled to undergo a low-back interventional procedure completed the PSQ-E and other questionnaires. Their data were compared with an age-, sex-, and opioid usage–matched sample of 57 self-identified non-Hispanic white (NHW) subjects. Pain ratings on a visual analog scale (VAS) were obtained following 2 standardized injections of subcutaneous lidocaine (VAS1—infiltration in hand, VAS2—infiltration of procedural site). Correlations between PSQ-E scores, VAS measures, and other inventories were tested. Results: The PSQ-E scores and clinical and experimental pain scores were all significantly elevated in AA compared with NHW patients ( P < 0.05 for experimental pain scores, P < 0.001 for PSQ and clinical pain scores). Measures of pain interference, depression, anxiety, and pain catastrophizing were not different between groups. Similar to our previous study, PSQ-E scores significantly correlated with both experimental and clinical pain scores (eg, PSQ-E with Brief Pain Inventory pain score: r = 0.39, P < 0.001). Conclusions: The study demonstrated significantly elevated pain sensitivity in AA compared with NHW patients as measured by the PSQ-E and experimental and clinical pain intensity scores. This shows that the PSQ reflects the known elevation of pain sensitivity in AA subjects and suggests that it may be useful in assessing pain treatment disparities by identifying and standardizing differences in pain sensitivity.